KINERJA BAURAN PEMASARAN PENALAMA COFFEE & TALK DI KOTA BOGOR BERDASARKAN PERSEPSI KONSUMEN - Friska Andriyani Lestari; Nia Rosiana (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
The increasing consumption of coffee in Indonesia is supported by the many coffee drink businesses, one of which is Penalama Coffee & Talk. Penalama Coffee & Talk experienced several problems, such as high competition for coffee products, competitive prices, located in remote places, promotions, late employees, SOP that are run inappropriately, and need improvements to supporting facilities. Therby requires evaluating marketing strategies to increase sales and satisfaction for consumers. Therefore, this study was conducted to analyze the performance of the marketing mix at Penalama Coffee & Talk. This research was conducted using descriptive analysis methods, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that consumer characteristics were dominated by consumers aged 17-25 years, men, domiciled in Bogor City, unmarried, working as private employees with income per month reaching >Rp5,000,000, the last education taken, namely academic education (S1/S2/S3), and the frequency of consumer visits 1-4 times / month. Based on CSI analysis obtained satisfaction results of 88.64 and IPA analysis obtained that location attributes became a top priority in performance improvement.